Effect of power variations across a fuel bundle and within a fuel element on fuel centerline temperature in PHWR bundles in uncrept and crept pressure tubes. (April 2017) - Onder, E.N.; Roubtsov, D.; Rao, Y.F.; Wilhelm, B.
Highlights: Pressure tube creep effect on fuel pin power and temperatures was investigated. Noticeable effects were observed for 5.1% crept pressure tube. Bundle eccentricity effect on power variations was insignificant for uncrept channels. Difference of 112 °C was observed between top & bottom elements in 5.1% crept channel. Not discernible fission gas release was expected with temperature difference of 112 °C. Abstract: The neutron flux and fission power profiles through a fuel bundle and across a fuel element are important aspects of nuclear fuel analysis in multi-scale/multi-physics modelling of Pressurized Heavy Water Reactors (PHWRs) with advanced fuel bundles. Fuel channels in many existing PHWRs are horizontal. With ageing, pressure tubes creep and fuel bundles in these pressure tubes are eccentrically located, which results in an asymmetric coolant flow distribution between the top and bottom of the fuel bundles. The diametral change of the pressure tube due to creep is not constant along the fuel channel; it reaches a maximum in the vicinity of the maximum neutron flux location. The cross-sectional asymmetric positioning of fuel bundles in a crept pressure tube contributes to an asymmetric power distribution within a ring of fuel elements. Modern reactor physics lattice codes (such as WIMS-AECL 1 ) are capable of predicting the details of power distribution from basic principles. Thermalhydraulics subchannel codes (such as ASSERT-PV) use models to describe inhomogeneous power distribution within and across fuel elements (e.g., flux tilt model, different powers in different ring elements, or radial power profiles). In this work, physics and thermalhydraulics codes are applied to quantify the effect of eccentricity of a fuel bundle on power variations across it and within a fuel element, and ultimately on the fuel temperature distribution and fuel centerline temperature, which is one of the indicators of fuel performance under normal operating conditions (NOC). Due to fissioning, Xe and Kr gases are produced, which contribute to the internal gas pressure within an element. The increase in gas pressure may jeopardize the fuel element integrity (sheath rupture). On the other hand, fission gas is produced as a function of neutron flux/power and diffuses to the grain boundaries and fuel-pellet interface as a function of fuel temperature. Therefore, it is important to know the fuel temperatures and distributions within the fuel.